2015
DOI: 10.2298/vsp131112035b
|View full text |Cite
|
Sign up to set email alerts
|

Validation and cross-cultural adaptation of the questionnaire ThyPRO in thyroid patients in Serbia

Abstract: The ThyPRO may be useful in measuring health-related quality of life in patients with thyroid disease in Serbia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
1
3
0
1
Order By: Relevance
“…The alpha coefficients suggest that the ThyPROro (85-item) and ThyPROro-39 are reliable instruments for evaluating QoL of patients with benign thyroid diseases. The values of Cronbach`s alpha in our study, being in the range 0.78-0.93 for the ThyPROro (85-item) and 0.78-0.87 for the ThyPROro-39, were comparable to previous findings (12,39). Watt et al reported a Cronbach`s alpha above 0.9, a very high reliability estimate, from 904 respondents (12).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The alpha coefficients suggest that the ThyPROro (85-item) and ThyPROro-39 are reliable instruments for evaluating QoL of patients with benign thyroid diseases. The values of Cronbach`s alpha in our study, being in the range 0.78-0.93 for the ThyPROro (85-item) and 0.78-0.87 for the ThyPROro-39, were comparable to previous findings (12,39). Watt et al reported a Cronbach`s alpha above 0.9, a very high reliability estimate, from 904 respondents (12).…”
Section: Discussionsupporting
confidence: 89%
“…Watt et al reported a Cronbach`s alpha above 0.9, a very high reliability estimate, from 904 respondents (12). Similarly, Branka et al showed reliability coefficients for Serbian patients in the range 0.83-0.95 (39). As usual 19) 42 ( 13) 41 ( 14) 24 ( 19) 27 ( 23) 25 ( 25) 21 (17) Toxic nodular goiter (n=9) 30 ( 16) 41 ( 17) 39 ( 18) 29 ( 26) 51 ( 13) 34 ( 24) 36 ( 28) 42 ( 14) 40 ( 14) 27 ( 20) 36 ( 21 20) 37 ( 16) 24 ( 20) 49 ( 9) 27 ( 22) 38 ( 25) 41 ( 12) 45 ( 14) 24 ( 21) 30 ( 26) 24 ( 27) 24 (16) Hashimoto's thyroiditis (n=46) 30 ( 21) 27 ( 20) 31 ( 25) 31 ( 23) 46 ( 9) 29 ( 25) 41 ( 29) 44 ( 17) 43 ( 16) 24 ( 25) 29 ( 26) 24 ( 23) 25 (24) Other thyroid disease (n=15) 24 ( 21) 37 ( 16) 39 ( 21) 26 ( 23) 46 ( 12) 24 ( 19) 40 ( 23) 44 ( 17) 42 (…”
Section: Discussionunclassified
“…One study using a Romanian version of the ThyPRO 30 found that the Cronbach α coefficients ranged from 0.78 to 0.93, and another using a Serbian version found that they ranged from 0.83 to 0.95. 31 There was no standard cut-point on the acceptable value of Cronbach α coefficients. However, the acceptable values in most reports were ranging from 0.70 to 0.95.…”
Section: Discussionmentioning
confidence: 99%
“…Like the original questionnaire 9 and other translated versions 29 , the ThyPROes demonstrated good quality measurement using classic procedures for reliability assessment. Additionally, following the methodology used for cross-cultural validation of other language versions 25 , we also evaluated DIF between the Spanish translated version and the Danish master questionnaire to investigate potential language bias.…”
Section: Discussionmentioning
confidence: 99%